E4F1 coordinates pyruvate metabolism and the activity of the elongator complex to ensure translation fidelity during brain development - Michela Di Michele; Aurore Attina; Pierre-François Roux; Imène Tabet; Sophie Laguesse; Javier Florido; Morane Houdeville; Armelle Choquet; Betty Encislai; Giuseppe Arena; Carlo De Blasio; Olivia Wendling; et al. (Nature Communications)
Abstract Pyruvate metabolism defects lead to severe neuropathies such as the Leigh syndrome (LS) but the molecular mechanisms underlying neuronal cell death remain poorly understood. Here, we unravel a connection between pyruvate metabolism and the regulation of the epitranscriptome that plays an essential role during brain development. Using genetically engineered mouse model and primary neuronal cells, we identify the transcription factor E4F1 as a key coordinator of AcetylCoenzyme A (AcCoA) production by the pyruvate dehydrogenase complex (PDC) and its utilization as an essential co-factor by the Elongator complex to acetylate tRNAs at the wobble position uridine 34 (U34). E4F1-mediated direct transcriptional regulation of Dlat and Elp3, two genes encoding key subunits of the PDC and of the Elongator complex, respectively, ensures proper translation fidelity and cell survival in the central nervous system (CNS) during mouse embryonic development. Furthermore, analysis of PDH-deficient cells highlight a crosstalk linking the PDC to ELP3 expression that is perturbed in LS patients.